Marine treatment of sewage and sludge proceedings of the conference organized by the Institution of Civil Engineers and held in Brighton on 29-30 April 1987. (Thomas Telford, 1988)
The sea's enormous capacity to absorb waste products is widely used throughout the world, but if this unique resource is to remain a healthy and effective method of disposal, it needs to be better understood. This book covers the various methods of marine treatment of sewage and sludge.